Benefits that Asthmatic Patients Receive after the Application of a Physiotherapeutic and Rehabilitative Treatment - Ismaray Sacerio González; Vivian Isabel Chávez Pérez; Belkis González Aguiar (Universidad de las Ciencias Médicas de Cienfuegos, 2023)
Bronchial asthma continues to be the most common chronic disease in childhood. Its prevalence continues to increase despite the fact that effective therapeutic manuals are currently available for the correct management of the main symptoms of the disease. The non-pharmacological treatment of this condition is based on three pillars: education about the disease, guides for professionals and patients, and respiratory physiotherapy. Patients who have regular physiotherapy and rehabilitation treatment have a significant improvement in asthma control, especially if these are practiced under the supervision of a physiotherapist. The benefits that asthmatic patients achieve with physiotherapy and rehabilitation are numerous and one of the most important effects is the positive impact on quality of life.